Diseño de gestión de inocuidad alimentaria ISO 22000:2005 en una empresa elaboradora de premezcla de panificación. - Riofrío, María Fernanda (2010)
This project reflects the establishment of the general guidelines of a Food Safety Management System, based on the ISO 22000:2005 on a firm that handles baking mixes. Initially an analysis of the manufacturing process from raw materials reception to finish product packaging took place. Then an interdisciplinary safety team was formed, this team had the responsibility and authority to monitor and manage the continuous improvement process of the food safety management system following international standards. The documentation of good manufacturing practices, sanitation standards operating procedures and the HACCP plan was the main task of the project. With the design and implementation of this standard, we sought to ensure a safe product for human consumption.